History, power, and identity : ethnogenesis in the Americas, 1492-1992 - Hill, Jonathan David, 1954- (University of Iowa Press, 1996)
For the past five centuries, indigenous and African American communities throughout the Americas have fought to maintain and recreate enduring identities under conditions of radical change and discontinuity. The essays in this ground-breaking volume document this cultural creativity - this ethnogenesis - within and against the broader contexts of domination; the authors simultaneously encompass the entanglements of local communities in the webs of national and global power relations as well as people's unique abilities to gain control over their history and identity.